Selecting a Dean of Faculty through a Partially Democratic Process to Improve Health Programs: Short Communication - Ali E. Oskouei (Tabriz University of Medical Sciences, 2014)
The Dean of Faculties is normally selected by the Chancellor of Universities. The democratic way of selecting a dean of faculties is an innovative procedure that first happened in 2013 at Tabriz University of Medical Sciences (TUMS). A brief survey of the faculties revealed that there were some disadvantages of this procedure. An insufficient number of candidates, obligation in nomination in some cases, casting ballots only by faculty members, and lack of future and strategic plans by candidates are some deficits in the process that brought some risk to the faculties and sometimes unrest to TUMS. These risks made the process more dangerous than it used to be previously, when we used more traditional ways of selecting a dean of faculty. In order to prevent possible risks to the faculty and university, we offer some suggestions to make the ground ready for democratic practices in selecting a dean of faculty.